WARFARE : THE DEFINITIVE VISUAL HISTORY (DK Publishing, 2020)
Warfare traces the epic 5,000- year story of conflict from the earliest battles to the Syrian Civil War. Exploring the campaigns and causes, the warriors and commanders, and the tactics, weapons, and technology that have shaped warfare worldwide, this is an updated edition of the definitive visual guide to a brutal, intense, and often heroic dimension of the human story